2022
DOI: 10.1142/s2010495222500221
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Economic Freedom and Its Subcomponents on Commercial Banks’ Risk-Taking

Abstract: We hypothesize that both liberalization and economic freedom are double-edged swords for the banking industry because they can increase both stability and fragility of the banks. To test our hypotheses, we use the two-step GMM technique to examine the impact of economic freedom and the impacts of all of its sub-components on the risk-taking behavior of US commercial banks for the period from 2003 to 2019. We find that economic freedom adversely affects banks’ risks, and therefore, increases the stability of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 67 publications
0
2
0
Order By: Relevance
“…Studies have shown that entrepreneurs motivated by opportunities generally experience greater level for the subjective well-being than those motivated by needs. However, entrepreneurs driven by necessities report similar levels of happiness (Abbas et al, 2022;Gohar et al, 2022). In competitive markets, inventive and imitative entrepreneurship are significant because they enhance and refine established products and services, diminish expenses, expand consumer accessibility, and ultimately elevate individuals' quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Studies have shown that entrepreneurs motivated by opportunities generally experience greater level for the subjective well-being than those motivated by needs. However, entrepreneurs driven by necessities report similar levels of happiness (Abbas et al, 2022;Gohar et al, 2022). In competitive markets, inventive and imitative entrepreneurship are significant because they enhance and refine established products and services, diminish expenses, expand consumer accessibility, and ultimately elevate individuals' quality of life.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Therefore, the study investigates how corporate social responsibility affects financial and non-financial performance [ 1 , 2 ]. Banks measure their financial performance through various means such as asset evaluation, efficient risk management, and offering innovative financial products in the modern era [ [3] , [4] , [5] ]. However, empirical evidence has shown that non-financial performance plays a critical role in stakeholder perceptions in today's highly competitive environment.…”
Section: Introductionmentioning
confidence: 99%